Mengembangkan Rubrik Penilaian Praktis yang Efektif: Pendekatan Komprehensif untuk Meningkatkan Evaluasi Hasil Pembelajaran dalam Pendidikan - Ihwan Mahmudi; Ayu Nurbaha; Siti Fadilah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
The process of assessing learning outcomes is an important component that is inseparable in the world of education, the quality of the measuring instrument guarantees the validity of an assessment result, if the assessment instrument is valid and reliable it will also produce an effective assessment. The aims of this study is to understand how to develop practical assessment rubric techniques. This study used library research with data collection techniques in the form of books, magazines, and documents related to the content analysis approach. The results of this study is the practical assessment rubric is structured based on the sequence of rubric components, including determining Task Descriptions, Assessment Scales, Assessment Dimensions (Indicators), and Dimension Descriptions (Criteria) as a reference for assessment. Simply incorporating these four aspects in developing the practical assessment rubric is not enough. To meet the standards of objective assessment, the rubric needs to be tested.